PBPK modeling demonstrates that exposure time adjustment is unnecessary for setting an acute manganese inhalation exposure guideline - Camarie S. Perry; Ann H. Verwiel; Tammie R. Covington; Deborah M. Proctor (Regulatory Toxicology and Pharmacology, 2024)

Use of physiologically based pharmacokinetic modeling to support development of an acute (24-hour) health-based inhalation guideline for manganese - Camarie S. Perry; Alexander D. Blanchette; Stephanie N. Vivanco; Ann H. Verwiel; Deborah M. Proctor (Regulatory Toxicology and Pharmacology, 2023)

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

A randomized, placebo-controlled, phase 1 study to evaluate the effects of TAK-063 on ketamine-induced changes in fMRI BOLD signal in healthy subjects - Deborah A. Yurgelun-Todd; Perry F. Renshaw; Paul Goldsmith; Tolga Uz; Thomas A. Macek (Psychopharmacology, 2020)
Rationale Phosphodiesterase 10A inhibitor TAK-063 has shown effects that suggest efficacy in schizophrenia treatment. Objective This randomized, double-blind, placebo-controlled, incomplete-crossover study investigated effects of single oral administration of TAK-063 on ketamine-induced changes in blood oxygen level-dependent (BOLD) signal in healthy males. Methods Healthy men aged 18 to 45 years with normal magnetic resonance imaging (MRI) scans and electroencephalogram measurements at screening were eligible. Each subject was randomized to one of nine treatment schedules: all subjects received placebo and two of three doses of TAK-063 followed by ketamine. The primary endpoint was ketamine-induced brain activity in select regions of the brain during resting state. Secondary endpoints included pharmacokinetic parameters of TAK-063, proportion of subjects with treatment-emergent adverse events (AEs), and percentage of subjects meeting criteria for abnormal safety laboratory tests and vital sign measurements. Results The study comprised 27 subjects. Prior to ketamine infusion, TAK-063 exerted region-specific effects on resting state functional MRI (fMRI) BOLD signal. After ketamine administration, TAK-063 reduced the Cohen’s effect size for resting-state fMRI BOLD signal in key brain regions examined, and exerted similar effects on BOLD signal during the working memory task across all doses. TAK-063 was safe and well tolerated. Conclusions Our results are consistent with non-clinical studies of ketamine and TAK-063 and clinical studies of ketamine and risperidone. It is unknown whether these data are predictive of potential antipsychotic efficacy, and further analyses are required.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Adult-onset opsoclonus-myoclonus syndrome due to West Nile Virus treated with intravenous immunoglobulin - Julien Hébert; David Armstrong; Nick Daneman; Jennifer Deborah Jain; James Perry (Journal of NeuroVirology, 2017)

Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - David A. Siegel; Ken O. Buesseler; Michael J. Behrenfeld; Claudia R. Benitez-Nelson; Emmanuel Boss; Mark A. Brzezinski; Adrian Burd; Craig A. Carlson; Eric A. D'Asaro; Scott C. Doney; Mary J. Perry; Rachel H. R. Stanley; et al. (Frontiers in Marine Science, 2016)

Importance of Biogeomorphic and Spatial Properties in Assessing a Tidal Salt Marsh Vulnerability to Sea-level Rise - Karen M. Thorne; Deborah L. Elliott-Fisk; Glenn D. Wylie; William M. Perry; John Y. Takekawa (Estuaries and Coasts, 2014)

FUS Immunogold Labeling TEM Analysis of the Neuronal Cytoplasmic Inclusions of Neuronal Intermediate Filament Inclusion Disease: A Frontotemporal Lobar Degeneration with FUS Proteinopathy - Tristan Page; Michael A. Gitcho; Sabrina Mosaheb; Deborah Carter; Sumi Chakraverty; Robert H. Perry; Eileen H. Bigio; Marla Gearing; Isidre Ferrer; Alison M. Goate; Nigel J. Cairns; Julian R. Thorpe (Journal of Molecular Neuroscience, 2011)

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Prefrontal and temporal gray matter density decreases in opiate dependence - In Kyoon Lyoo; Mark H. Pollack; Marisa M. Silveri; Kyung Heup Ahn; Claudia I. Diaz; Jaeuk Hwang; Seog Ju Kim; Deborah A. Yurgelun-Todd; Marc J. Kaufman; Perry F. Renshaw (Psychopharmacology, 2006)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)